Trends in the development of medical science and technology at the beginning of the 21s1 century - T. Jacob, T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
Mau is the only creature that could think about his future, and therefore, prepares for it and actually shapes it, or even invents his future. Predictions about the future are more relevant nowadays because of the importance of intergenerational justice, of learning from history and of adaptational preparation in view of rapid technological changes. Scientific and technological development will unavoidably influence the course of medical sciences and practice. The sociocultural impact of this development will affect even the essence of life itself, not only the human society, food strategy, demography, disease pattern, and environment. Most important is the impact on ethics and religion, creating frustration, uncertainties, emptiness and insecurity in life which consequently demands the revival of both and assure their existence in the next century. It is suggested that scientific ethics will be intensified, religious interpretations adjusted to the development of civilization without deviating from its basic principles, and that a new paradigm in medicine is needed in order to restore the disequilibrium brought forth by the culture of overconsumption and overcompetition. Key Words: futuristics - medical sciences - technological impact = ethics - religion